(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To generate human liver cancer tumors in immunodeficient mice (nude mice) using the human liver cancer cell line Hep-3B. Methods: Cultivation and proliferation of Hep-3B human liver cancer cells, transplantation of 106 Hep-3B cells under the skin of each nude mouse thigh, monitoring mouse condition, formation and development tumor for 35 days. Determine the tumor growth rate, tumor regression rate, tumor volume, survival - death rate, and pathological images of the tumor. Results: Successfully cultured and proliferated human liver cancer cells of the Hep-3B line, enough cells to serve tumor grafting on nude mice. When transplanting human liver cancer cells from the Hep-3B line, the tumor appearance rate reached 87.5% after 7 days of transplantation, the tumor regression rate was 0%, the average tumor volume after 35 days of transplantation was 774.8 mm3. No mice died due to technical errors and throughout the experiment, the pathological images were similar to human tumors. Conclusion: Creating an immune-deficient mouse model carrying human liver cancer of the Hep-3B line.